The Influence of Social Background on Participation in Adult Education: Applying the Cultural Capital Framework. (May 2016) - Cincinnato, Sebastiano; De Wever, Bram; Van Keer, Hilde; Valcke, Martin
In this article, we address the issue of participation in adult education building on the cultural capital framework. This theoretical framework suggests that (educational) practices are affected by one's social background and, more precisely, by the cultural resources handed down in the family context. To examine the validity of this theoretical framework, we build on data from the Programme for the International Assessment of Adult Competencies from 23 countries ( n = 120, 789). The Programme data allow using the variables parents' educational level (a proxy for social background), educational attainment, and readiness to learn as precursors of participation in adult education (both a proxy for cultural capital). Our findings suggest that the cultural capital framework is not fully suited to explain participation in adult education: Although social background has an (indirect) influence on participation, its effect does not concur with theoretical predictions, that is, mediated by the readiness to learn.